AUGMENTED REALITY MOBILE APPLICATION AS AN ANIMAL INTRODUCTION LEARNING MEDIA FOR ELEMENTARY SCHOOL STUDENTS WITH MENTALLY DISABLED - Nanny Raras Setyoningrum; Hendi Setiawan; Danandjaya Saputra (Jurnal Media Elektrik, 2024)
Mental disability is a disorder in mental development that is usually characterized by a level of intelligence that is below the average of normal children, so mentally disabled children require a different learning approach because of their unique characteristics. The disability rate statistics for children aged 5-19 years is 3.3%. Meanwhile, the total population at that age (2021) is 66.6 million. Data from the Ministry of Education and Culture as of August 2021 states that the number of students attending SLB or inclusion schools is 269,398 children. The obstacle complained about by teachers in providing learning for children with special needs (with mentally disabled) is that teachers have difficulty delivering learning material because children with special needs find it difficult to understand what the teacher is conveying so they need help using effective and efficient learning media, for example learning media that uses augmented reality technology. This research aims to design a mobile-based application as a learning medium for animal recognition for mentally disabled students using augmented reality technology. This research method uses research and development research. The results of the research are an augmented reality application called ARAnimal which can visualize pets from two-dimensional images into 3D objects, besides that it can also provide a description of the animal's physical characteristics using audio. There is a quiz feature in the form of completing animal names and pairing animal names with types of pets or wild animals. With this application, student learning becomes interactive and interesting and helps teachers in delivering animal introduction material.